Targeting Gut Bacteria Using Inulin‐Conjugated Mesoporous Silica Nanoparticles (Adv. Mater. Interfaces 14/2022). Issue 14 (13th May 2022) - von Baeckmann, Cornelia; Riva, Alessandra; Guggenberger, Patrick; Kählig, Hanspeter; Han, Seung Won; Inan, Deniz; Del Favero, Giorgia; Berry, David; Kleitz, Freddy
Abstract : Inulin‐Conjugated Mesoporous Silica Nanoparticles In article number 2102558, Cornelia von Baeckmann, David Berry, Freddy Kleitz, and co‐workers demonstrate the possible application of inulin‐conjugated mesoporous silica nanoparticles (pink) for targeting the human gut bacteria (blue). Accumulation of the bacteria on the nanoparticles are highlighted, paving the way for a system to actively influence the bacteria composition in the microbiome once it is loaded with anti‐microbials. TEM of the conjugate and a structured illumination microscopy image are shown.